ASPECTS OF ARMY ROAD TRANSPORT MANAGEMENT - Japhet, M. (Scientia Militaria - South African Journal of Military Studies, 2012)
A basic tenet of transport management must be the efficient operation of all constituent parts of the transport function. In recognition of the growing urgency of the energy problem as a primary goal and of the need to maintain a high level of combat readiness at the same time, this article will look, albeit briefly, at the various aspects of road transport that need to be dealt with in the search for cost-effectiveness. Five major elements of road transport management are: Purchasing policy; maintenance; driver training and control; movements planning and procedures; and Research and Development.